URGENSI RATIFIKASI PERJANJIAN BANTUAN HUKUM TIMBAL BALIK DALAM MASALAH PIDANA MELALUI KEPUTUSAN PRESIDEN TERHADAP PENGEMBALIAN ASSET-ASSET HASIL KEJAHATAN TINDAK PIDANA KORUPSI ANTARA REPUBLIK INDONESIA DAN KONFEDERASI SWISS : Array - Herman Katimin; Dewi Mulyanti; Iis Yeni Idaningsih; Amir Hussein Saleh (Program Studi Hukum Program Pasca Sarjana, 2020)
After the international agreement on Reciprocal Assistance in Criminal Matters between the Republic of Indonesia and the Swiss Confederation on 4 February 2019 in order to speed up criminal law processes in the Requesting State, at the level of implementation it is still not effective and there are no concrete steps in returning assets resulting from corruption in Switzerland. From these problems, the research method used is normative legal research by reviewing and analyzing international law and national law, including the agreement concerned. The results of the discussion are that in substance the agreement does not specifically or specifically confirm the resolution of the dispute and does not formulate provisions for ratification. In addition, it takes a long time to ratify the agreement into law through the DPR's approval process. Therefore, the substance of the agreement needs to be amended again and in a state of urgency by observing the principle of pacta servanda and the principle of freie emmessen. The ratification of the agreement should be through a presidential decree or presidential regulation to assist state resources in sustainable development and to be able to prosper the people, nation and Indonesian state.